The Effect of Leadership, Work Environment, Job Satisfaction,and Organizational Culture on Employee Performance of the West Lombok General Election Supervisory Agency (Bawaslu) - Hidayat, Surahman; Nuraulia, Ajeng; Irianto (Fakultas Agama Islam Universitas Islam Al-Azhar, 2024)
This study aimed to determine the influence of leadership, work environment, job satisfaction, and organizational culture on employee performance at BAWASLU LOBAR. It was associative research using a quantitative approach. The independent variables were leadership, work environment, job satisfaction, and organizational culture. The dependent variable was employee performance. The population was 55 employees and supervisory officers of BAWASLU LOBAR. Data was collected through distributing 55 questionnaires and analyzed using multiple linear regression in SPSS 23. The results showed that leadership and organizational culture had a significant positive effect on employee performance. Meanwhile, the work environment and job satisfaction had little effect. The study found that the four independent variables could influence employee performance by 39.4%, while the remaining 60.6% was influenced by other external variables not included in the regression model. In conclusion, leadership and organizational culture most impacted employee performance at BAWASLU LOBAR.